Treatment of Reused Oil by Thermal Conversion Process - Obeyed, Saleem Mohammed; Ali, Israa Shaker; Ehsan, Ali (Al-Nahrain Journal for Engineering Sciences, 2017)
This work deals with treatment ofused lubricant oils whichare accumulate from automotive engine, bythermal conversion process. The used lubricant oil for two samples is fractionated by the atmospheric distillation device into fractions, (waste oil liquids and residue). Which are carried out at atmospheric pressure and temperature up to 350 ºC._x000D_ The conversion which was obtained from these fractions was (92 and95) % respectively for these two samples._x000D_ The fractionated waste oil liquids products fromatmospheric distillationdeviceare fractionated alsoto light fractions (gasoline, kerosene, gas oil) and residue for these two samples at atmospheric pressure according to their boiling point.These fractions for these two samples are also distillated inatmospheric distillation device, in order to calculatesome important physical and chemical properties (Mean average boiling point, specific gravity, flash point, aniline point, smoke point, molecular weight) of these fractions, to comparison with standardphysical and chemical properties, alsostudying the possibilities of industrial uses for these fractions._x000D_ The yield of gas oil for the first samplein waste lubricant oilisabout 50%, more than gasoline 15% and kerosene 30%from 100 ml of treatment waste lubricant oil, and more identical curve from gasoline and kerosene curve._x000D_ Also for the second sample, the yield of gas oil is the largest quantity 43%fromtheyield of gasoline 15% and yield of kerosene 35% from 200 ml of treatment waste lubricant oil, and more identical curve with kerosene from gasoline curve.